2019
DOI: 10.1002/cb.1774
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents of consumers' citizenship behaviour towards organic foods

Abstract: Within the consumer behaviour literature, there has been little research on factors that influence customers' choices for organic foods. This study investigates three aspects of the Taiwanese organic food market. The first aspect considers how argument quality, source credibility, and social comparison affect consumer‐social venture identification. The second aspect examines how identity attractiveness, social media engagement, and self‐determination affect personal relevance. The third and final aspect invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 113 publications
(174 reference statements)
0
15
0
Order By: Relevance
“…Grounded in the social exchange theory, helping behaviours are viewed as a dimension of citizenship behaviour that are voluntary in nature and provide assistance to others (Bove et al 2009;. Even though citizenship behaviour is a contemporary topic (Chiu et al 2019;Godwin & Wright 2019), the helping behaviour dimension has received limited attention within the online environment. Commitment, grounded in relationship marketing, has been established as an antecedent of citizenship behaviour (Hashim & Tan 2015;Yong, Sachau & Lassiter 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Grounded in the social exchange theory, helping behaviours are viewed as a dimension of citizenship behaviour that are voluntary in nature and provide assistance to others (Bove et al 2009;. Even though citizenship behaviour is a contemporary topic (Chiu et al 2019;Godwin & Wright 2019), the helping behaviour dimension has received limited attention within the online environment. Commitment, grounded in relationship marketing, has been established as an antecedent of citizenship behaviour (Hashim & Tan 2015;Yong, Sachau & Lassiter 2011).…”
Section: Introductionmentioning
confidence: 99%
“… Tando et al (2020) showed a significant influence of intrinsic motivation and integrated and external regulation on consumer attitude and buying behavior of organic food. Chiu et al (2019) found that self-determination has a positive influence on personal relevance, which positively affects customer citizenship behavior toward organic food. Schösler et al (2014) indicated that internalized motivation is the main factor that makes a difference in the intrinsic enjoyment of cooking and eating behavior.…”
Section: Theories and Hypothesesmentioning
confidence: 97%
“…The chain mediating role of PT, EC and SAT is played in the AGR-CCB and also EXT-CCB associations respectively. (Assiouras et al, 2019), argument quality, and source credibility (Chiu et al, 2019). The last aspect includes community features, such as encounter-oriented e-retailing environments (Anaza & Zhao, 2013), perceived community-brand similarity (Hsu et al, 2015), and community social support (Zhu et al, 2016).…”
Section: Nomentioning
confidence: 99%
“…A review of empirical studies has suggested that identified antecedents can be classified into four types. The first type pertains to psychographic factors of customers, including extraversion and agreeableness (Anaza, 2014), pride and mindfulness (Hwang & Lee, 2019), justice perception (Yi & Gong, 2008), identity attractiveness, social media engagement, self‐determination (Chiu et al, 2019) and participation in crowdsourcing (Yuksel et al, 2018). The second captures the aspects of peer customers, including their citizenship behaviors (Yi et al, 2013) and passion (Kim et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation